Review on Analytical Method Validation on Tirzepatide - Asmita Mishra; Vipal Patel; Binal Prajapati; Helly Shah (Asian Journal of Pharmaceutical Research and Development, 2025)
Background: - Type 2 diabetes mellitus (T2DM), obesity, cardiovascular diseases in T2DM, heart failure, non- alcoholic steato hepatitis, obstructive sleep apnea, and obesity-related mortality and morbidity are among the conditions for which Eli Lilly is developing Tirzepatide. As a supplement to diet and exercise, Tirzepatidewas initially approved in the USAin May2022 to help adults with type 2 diabetes improve their glycaemic control. Tirzepatide is a novel antidiabetic medication, single-molecule agonistoftheglucose-dependentinsulinotropicpolypeptideandglucagon-like peptide-1 receptors. It is marketed under the brand names MOUNJARO and ZEPBOUND. Method:-Techniques such as Reversed-phase High-performance liquid chromatography (RP-HPLC), High-performance liquid chromatography (HPLC), Ultraviolet spectroscopy (UV spectroscopy), Fluorescence spectroscopy, and others have been used for analysis. Conclusion: - An HPLC Method Validated using a Quality-by-Design (QBD) approach concludes that the method is linear, accurate, precise, and robust for the Quality control of tirzepatide in bulk and dosage forms and LC-MS bioanalytical method for quantifying tirzepatide in human plasma is typically concluded to be specific, sensitive, and accurate for pharmacokinetic studies.